Economics in the world of education: Its goals and benefits in the scope of educational economics - Fajriyatul Izzah; Holilur Rahman (Penerbit Hellow Pustaka, 2024)
Economy is a very important thing in human life because with economy human can fulfill their life needs well, and education is also an important thing in human life because by getting good economy human need knowledge or provision to make their life prosperous and education can also raise human status itself from the perspective of majority of human itself or it can be said that both are the benchmark of human success. The purpose of this study is to find out the purpose and role or benefits of education economy. This research method uses library research method or also called Library Resarch, Data sources used in this study are books, journals, articles, papers and Al-Qur'an that are related to Islamic education economy. And the result of this study is the purpose of Islamic education economy first to prosper the economy Second to form a fair social order of society by preparing human resources who are moral, knowledgeable, and insightful. Third to achieve fair and equitable distribution of income and wealth, and to get this also requires quality and professional human resources and this can be obtained from economic education in the world of education. The fourth is to create freedom for individuals or to empower individuals and groups that promote skills, intelligence and social responsibility. And the role or benefits of Islamic education economy is to prosper the education economy sector.